Did somebody say totalitarianism? : five interventions in the (mis)use of a notion - Žižek, Slavoj (Žižek, Slavoj., 2002)
In some circles, a nod towards totalitarianism is enough to dismiss any critique of the status quo. Such is the insidiousness of the neo-liberal ideology, argues Slavoj Zizek. Did Somebody Say Totalitarianism? turns a specious rhetorical strategy on its head to identify a network of family resemblances between totalitarianism and modern liberal democracy. Zizek argues that totalitarianism is invariably defined in terms of four things: the Holocaust as the ultimate, diabolical evil; the Stalinist gulag as the alleged truth of the socialist revolutionary project; ethnic and religious fundamentalisms, which are to be fought through multiculturalist tolerance; and the deconstructionist idea that the ultimate root of totalitarianism is the ontological closure of thought. Zizek concludes that the devil lies not so much in the detail but in what enables the very designation totalitarian: the liberal-democratic consensus itself. -- Publisher description.